Relevansi Konsep Pendidikan Multikultural dalam Perspektif Al-Quran di Era Kontemporer - Zuhari Harsyah (Social Science Academic, 2023)
This paper aims to present a complete abstract of the concept of multicultural education in the perspective of the Koran. This article uses the literature review method by analyzing the verses of the Koran related to multicultural education. The introduction describes the notion of multicultural education and its importance in the context of contemporary challenges. The method used is an analysis approach to verses of the Koran that are relevant to multicultural education. The results of the analysis show that the Al-Quran clearly emphasizes the importance of knowing, understanding, and respecting the diversity of cultures, ethnicities, and religions. Verses related to multicultural education emphasize the values of inclusion, tolerance, respect for differences, and human brotherhood. Discussion and analysis link the concept of multicultural education in the Koran with contemporary challenges such as globalization, multiculturalism, prejudice, discrimination, identity, and cultural amalgamation. This article also discusses the application of multicultural educational practices that involve an inclusive curriculum, diverse teaching methods, development of multicultural attitudes, training of educators, parental and community participation, and respect for language and cultural identity. In conclusion, this article emphasizes that multicultural education in the perspective of the Koran has significant relevance in dealing with contemporary challenges. This concept can be applied through a variety of practices, including an inclusive curriculum, diverse teaching methods, development of multicultural attitudes, training of educators, parental and community participation, and respect for language and cultural identity. In the context of multicultural education, the Koran provides solid guidelines for building a society that is inclusive, tolerant and respects diversity. Further research and implementation of multicultural educational practices from the perspective of the Koran can make an important contribution in creating a harmonious society in an increasingly multicultural global era.